Characterization of eucalyptus clones subject to wind damage - Zanuncio, Antônio José Vinha; Carvalho, Amélia Guimarães; Carneiro, Angélica de Cassia Oliveira; Valenzuela, Paulina; Gacitúa, William; Leite, Fernando Palha; Colodette, Jorge Luiz (Pesquisa Agropecuária Brasileira, 2017)
The objective of this work was to test a new methodology to assess the resistance of trees to wind damage and determine the characteristics that increase clone resistance to winds. Tree resistance to breakage, basic density, ultrastructure, anatomy, mechanical properties, and wood growth stress have been evaluated in seven Eucalyptus grandis × Eucalyptus urophylla clones, collected from a region with a high incidence of wind damage. The Pearson correlation coefficient between the tree resistance to breakage and the ratio between the area damaged by the winds and the total planted area was -0.839, showing the efficiency of the methodology adopted and that high breaking strength results in a smaller area affected by wind damage. Trees with a high basic density, cell wall fraction, modulus of elasticity of the middle lamella and fibers, fiber hardness, modulus of rupture, growth stress and low microfibril angle and height and width of the rays showed greater resistance to wind damage. Therefore, the selection of clones with these features may reduce the incidence of damage by winds in Eucalyptus plantations.

O objetivo deste trabalho foi testar uma nova metodologia para avaliar a resistência das árvores aos danos causados pelos ventos e determinar as características que aumentam a resistência dos clones a estes danos. A resistência das árvores à ruptura e a tensão de crescimento, assim como a densidade básica, ultraestrutura, anatomia e propriedades mecânicas da madeira foram avaliadas em sete clones de Eucalyptus grandis x Eucalyptus urophylla, recolhidos de uma região com uma alta incidência de danos provocados pelo vento. O coeficiente de correlação de Pearson entre a resistência à ruptura da árvore e a relação entre a área danificada pelos ventos e a área total plantada foi -0,839, mostrando a eficiência da metodologia adotada e que alta resistência à quebra resulta em baixa área afetada por danos pelos ventos. Árvores com uma alta densidade básica, fração da parede celular, módulo de elasticidade da lamela média e fibras, dureza da fibra, módulo de ruptura, tensão de crescimento e baixo ângulo microfibrilar e altura e largura dos raios apresentaram maior resistência a danos causados pelo vento. Portanto, a seleção de clones com estas características pode reduzir a incidência de danos causados por ventos em plantações de eucalipto.
Keywords: Eucalyptus grandis × Eucalyptus urophylla; Basic density; Cell wall fraction; Cell wall ultrastructure; Fiber; Wood; Densidade básica; Fração de parede celular; Ultraestrutura da parede celular; Fibra; Madeira